L120 odissey: Gamification of the evaluative proposal in an art and new media subject (Revista de Ensino em Artes, Moda e Design, 2022)
The present work analyzes the gamification of the evaluative proposal elaborated during the year 2020  in the Laboratory I subject belonging to the Bachelor  of Electronic Arts of the National University of Tres de  Febrero (UNTREF). This laboratory is presented as  an initial curricular space whose main purpose is to  offer an introduction to electronic arts, creative programming and artistic experimentation. The  evaluative proposal, called Odyssey L120: the virtual  experience, was developed as a way to overcome the  following problems: the creative block before the  realization of an artistic project in an initial instance  of a university career; the isolation product of the  health emergency by COVID-19; the adequacy based  on the time needed to carry out the project; and  coherence with the contents and methodology worked on in the course. The proposal involved the  realization of a digital card reading with different  elements -visual, material, sound and textual- that  worked as triggers to create an artistic production for  the end of the course. The mechanics of the  game were structured based on a science fiction  narrative, a set of rules and a collaborative dynamic  between the participants. The experience result  shows great motivation among the students and a  particular focus on collaborative work as a result of  the network system. Among the main conclusions, it  is established that the strategies of the game -both  the opening of possibilities and the imposition of  limits- are valuable to structure instances of artistic  creation.
Keywords: Gamification; Higher education; Artistic education